First-principles study on CO oxidation on CuO(111) surface prefers the Eley−Rideal or Langmuir−Hinshelwood pathway. (14th May 2022) - Lin, Long; Shi, Pei; Yao, Linwei; Xie, Kun; Tao, Hualong; Zhang, Zhanying; Wang, Yanfang
Abstract: Using the first-principles approach, we investigated the electronic and chemical properties of cupric oxide CuO (110) and CuO (111) and substantiated their catalytic activity toward CO oxidation. It is found that CuO (111) surface is more stable than the CuO (110) surface. We firstly study that adsorption of CO and O2 on perfect, oxygen vacancies and Cu-anchored CuO (111) surface. It is found that adsorption of CO and O2 molecules are chemical. Then we selected the most stable adsorption structure of CO/O2 to investigated the CO oxidation mechanism on different surface, here we choose to study the Langmuir–Hinshelwood (LH) mechanism and Eley–Rideal (ER) mechanism. The results show that perfect and Ovacancy CuO (111) surface is more inclined to LH mechanism, while the Cu-anchored CuO (111) surface is more inclined to ER mechanism. The results show that CuO catalyst is very effective for CO oxidation. Our work provides a deep understanding for the search of economical and reasonable CO oxidation catalysts.